Analisis Pengaruh Inflasi, Nilai Tukar Rupiah, BI Rate, Jumlah Uang Beredar, dan Indeks Shanghai Stock Exchange terhadap Indeks Sri Kehati di Bursa Efek Indonesia Periode 2014-2019 - Hermawan, Tri Wisnu; Purwohandoko, Purwohandoko (Jurnal Ilmu Manajemen, 2020)
This study is to explain the analysis of the influence of inflation, exchange rates, BI Rate, money supply, and Shanghai Stock Exchange index toward the Sri Kehati index on the Indonesia Stock Exchange (BEI) for the period 2014-2019. Data were analyzed by using multiple linear analysis techniques and use SPSS 18 as statistical analysis software. The sample type used is saturation samples so that there are 72 data taken monthly from 2014-2019. The results of this study indicate that inflation and exchange rate have a significant negative relationship to the Sri Kehati index. Meanwhile, the Shanghai Stock Exchange index has a significant positive relationship with the Sri Kehati index. The rest variable BI rate and money supply have no significant relationship to the Sri Kehati index. All independent variables simultaneously affect the Sri Kehati index. Based on the calculation the Adjusted R square value is 0.279 which means that the movement of the Sri Kehati index is influenced by 28% by the variables in this study and 72% is explained by other variables outside this study. Therefore, further research is expected to add other potential independent variables. The implication from this research is that investors should pay more attention to the exchange rate, inflation, and the Shanghai Stock Exchange index before investing in the Sri Kehati index.